Adoption of advance manufacturing technologies in micro, small and medium enterprises of India. (1st January 2013) - Singh, Brijesh; Narain, Rakesh; Yadav, R.C.
Significant contribution of micro, small and medium-sized enterprises (MSMEs) in the nation's economy and its competitiveness can be enhanced by successful adoption of suitable advance manufacturing technologies (AMT). This paper is based on a survey of 84 Indian MSMEs. The findings suggest that use of AMT leads to significant quality improvements, decrease in rejection rate, and increase in sales and reduction in labour costs for their products. This, in turn, helps in maintaining and increasing their customer base. Despite the numerous advantages offered by AMT, the adoption of AMT in Indian MSMEs is still not appreciable owing to huge investments along with lack of awareness.